The importance of customer service and quality management in determining a firm's success - Azizan, Norizan; Yusof, Ab. Aziz (Institut Kajian Pengguna, Universiti Utara Malaysia, 2001)
Today's organizations must be able to adapt and keep abreast with the development and seize the opportunity and benefits to grow and succeed. The management must be sensitive and opened to changes to avoid uncertainties and confitsions about their roles and their customers needs and demands. Failure to act and respond to the changes will expose them to lot of risks, including losing customers' confidence. They must be able to serve their customers more effectively and efficiently. Implementing a quality management system in an organization is a challenge. Despite numerous hurdles, quality management is still being considered as something that is needed for long-term solutions and customer-driven strategies. This paper focuses on the importance of customer service and quality management in a organization, specifically on achieving continuous improvement through quality customer service. Specific topics include initiating and implementing a quality management program, building a continuous improvement climate, applying quality principles and techniques, and performance appraisal vs. quality management.